2010
DOI: 10.1111/j.1526-4610.2010.01669.x
|View full text |Cite
|
Sign up to set email alerts
|

The Lack of Peripheral Pathology in Migraine Headache

Abstract: This article reviews the baffling problem of the pathophysiology behind a peripheral genesis of migraine pain--or more particularly the baffling problem of its absence. I examine a number of pathophysiological states and the effector mechanisms for these states and find most of them very plausible and that they are all supported by abundant evidence. However, this evidence is mostly indirect; to date the occurrence of any of the presumed pathological states has not been convincingly demonstrated. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 155 publications
(210 reference statements)
1
21
0
1
Order By: Relevance
“…This study provides the basis for a possible direct central top-down triggering of the migraine pain, at least in part independent by the peripheral trigeminal arm involvement, possibly mediated by the recurrent suppression of a central inhibitory modulation of trigeminal nuclei neurons and ultimately leading to the transmission of even ordinary and usually not perceivable trigeminal ''noise'' signals. This perspective fully complies with the concept that, besides the countless research efforts, no evidence has ever been found supporting a defined ''pathology'' distinguishing migraine from healthy individuals [35].…”
Section: New Evidences On the Cortical Spreading Depression Role In Msupporting
confidence: 60%
“…This study provides the basis for a possible direct central top-down triggering of the migraine pain, at least in part independent by the peripheral trigeminal arm involvement, possibly mediated by the recurrent suppression of a central inhibitory modulation of trigeminal nuclei neurons and ultimately leading to the transmission of even ordinary and usually not perceivable trigeminal ''noise'' signals. This perspective fully complies with the concept that, besides the countless research efforts, no evidence has ever been found supporting a defined ''pathology'' distinguishing migraine from healthy individuals [35].…”
Section: New Evidences On the Cortical Spreading Depression Role In Msupporting
confidence: 60%
“…The experiments reported here [part of a previously foreshadowed programme (11)] show that CSD -which could be either a trigger or a symptom of migraine (or both) -can generate sensory traffic in second-order sensory neurons independent of the generation of traffic in the first-order neurons which impinge upon them. These conclusions are fairly robust, but are subject to some limitations, summarized as: the experiments were conducted in anaesthetized rats; it is not known whether CSD produces pain in rats and; it is not known whether the neurons involved in this study are the same types of neurons as those involved in the perception of migraine pain in humans.…”
Section: Discussionmentioning
confidence: 95%
“…These include inflammatory mediators and agents that are released during neurogenic inflammation, cortical spreading depression (CSD), or both (22). According to an alternative central mechanism, defective processing in the CNS could lead to the perception of non-noxious trigeminovascular input as painful (23). Within the trigeminal nerve, the most abundant neuropeptide is CGRP, which is expressed in 35--50% of neurons in the trigeminal ganglia (24).…”
Section: Migraine: Much More Than a Headachementioning
confidence: 99%